2023
DOI: 10.1111/pbi.14102
|View full text |Cite
|
Sign up to set email alerts
|

SLG2 specifically regulates grain width through WOX11‐mediated cell expansion control in rice

Abstract: SummaryGrain size is specified by three dimensions of length, width and thickness, and slender grain is a desirable quality trait in rice. Up to now, many grain size regulators have been identified. However, most of these molecules show influence on multi‐dimensions of grain development, and only a few of them function specifically in grain width, a key factor determining grain yield and appearance quality. In this study, we identify the SLG2 (SLENDER GUY2) gene that specifically regulates grain width by affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 63 publications
(150 reference statements)
0
4
0
Order By: Relevance
“…Transcriptomic analysis of A. thaliana seeds revealed the participation of WOX11 in the regulation of seed dormancy and germination [ 14 ]. In rice, WOX11 interacts with SLENDER GUY2 and regulates grain width [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptomic analysis of A. thaliana seeds revealed the participation of WOX11 in the regulation of seed dormancy and germination [ 14 ]. In rice, WOX11 interacts with SLENDER GUY2 and regulates grain width [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several AtWOX genes are essential for multiple processes of tissue formation, including AtWUS and PRS1/AtWOX3 in the shoot apical meristem (STM) [13,14], AtWOX2 in the egg cell and zygote [15], AtWOX6 in the ovule development [16], STIP/AtWOX9 in STM, the root and other aerial organs [17], and At-WOX13 in floral transition [18]. In a model rice plant, the interaction of OsWOX11 and SLG2 determined grain width and affected quality traits [19]. Variation in the gene expression level of OsWUS negatively affects the phenotypic traits in rice [20].…”
Section: Introductionmentioning
confidence: 99%
“…PgWOX11 binds to the PgCLE45 promoter to regulate adventitious root branching (Liu et al, 2020). A new study shows that OsWOX11 works together with OsSLG2 regulate grain width by affecting the expansion of cells within the spikelet shell in rice (Xiong et al, 2023). Liao et al(2023) found that WOX11 regulates seed dormancy through mediating phytochrome B (PHYB) signaling during the induction stage.…”
Section: Introductionmentioning
confidence: 99%